Assessing Indian Ocean Economics: Perspective from Pakistan - Zaeem Hassan Mehmood; Ramla Khan (Department of International Relations, Universitas Andalas, 2021)
The Indian Ocean offers the “global commons” the sea lanes of communication that connects the East with the West. These SLOCs nurtures the global economic world by providing for a classical instance of ‘multilateral maritime matrix,’ whereby merchant ships are manufactured in one country, maintained and owned by another, underwritten by third, registered in fourth and crewed by subjects of another. In this regard, the strategic and commercial concerns of nation-states extends from its immediate maritime borders to the protection of chokepoints where merchandise is most vulnerable to array of contemporary security threats. The third largest ocean, since the cessation of bipolar hostilities after the end of the Cold War, has been integrated to global market economics to a critical extent whereby any interruptions to the established trade networks is likely to have a ‘shockwave effect’. The Indian Ocean is presaged to continue as a ‘central shipment pathway’ for regional and inter-continental trade in wide scope of commercial commodity items. The patterns observed in the region consists of up gradation of existing port infrastructure and developing export markets and resources based on blue economy would strengthen maritime ties. These transformations have the potential to permit the Indian Ocean to be the “strategic heart of the maritime world”.